Does ski width influence muscle activity and ski actions in an elite skier? A case study - Seifert, J.; Nunnikhoven, H.; Snyder, C.; Kipp, R. (Science and Skiing VII, 2018)
Alpine skiing is a complex activity where internal and external factors act on the skier and influence skiing performance. Internal factors include muscle activity and psychological aspects whereas external factors Include turn parameters, snow conditions, and slope of the run (Seifert et al., 2009). Muscular responses are not only dictated by these factors, but by equipment as well. Wide skis, for example, were originally designed for off-piste powder skiing. However, wide skis are gaining in popularity and are now found routinely on groomed runs. However, there is not a standard industry definition of what width constitutes a wide ski. It stands to reason that a wide ski could substantially change skiing technique as well as how these skis respond on the snow compared to a narrow ski. A wide ski can add upwards of 20-60 mm of underfoot width compared to a narrow ski. While the potential for skiing powder may be enhanced, the extra width also adds a longer lever arm in which the skier has to produce force to overcome when skiing on a groomed run. Zorko et al. (2015) reported on knee kinematics, comparing skis of different widths on a groomed run. They found greater knee extension and knee rotation with wide skis compared to narrow skis. How wide skis (WS) affect muscle action is not known. The purpose of this case study was to compare the differences in muscle activity and ski and skier actions in an elite-level skier when skiing on narrow (SL) and wide (WS) width skis.